Penguatan Profil Pelajar Pancasila Pada Kurikulum Merdeka Di Sma Swasta Persiapan Stabat - Zulham Siregar; Kahar Mashuri; Yusda Novianti; Eka Darliana; Anisa Noverita; Zikri Adha (Jurnal Pengabdian Kepada Masyarakat, 2022)
The problems faced in this 4.0 era are that students are required to be able to use information technology, but the quality of human resources must be further improved in order to be able to adapt to changes. This article is the result of community service which aims to express the challenges of social studies education in facing the era of the industrial revolution 4.0. The results of this study reveal that social studies education as a provision in facing changing times, social studies teaching is not only a concept or theory, but the implementation of social studies education is a guide for students to be able to solve social problems. Social studies teaching must transform into engaging and fun learning, creative, fostering high curiosity, critical thinking, opinion, collaboration in teams, social sensitivity, and problem-solving skills. The role of social studies education is not only to make students smart, but also to become good citizens, have a social spirit, character, and character. Therefore, in facing challenges in this era, collaboration between all parties is needed, including: schools, families, communities, and the government in order to improve the quality of education in the era of the industrial revolution 4.0.